Hubungan Higiene Sanitasi Dengan Keberadaan Bakteri Escherichia Coli Pada Depot Air Minum Isi Ulang Di Kawasan Universitas Muhammadyah Surakarta - Rosyani, Arnis Putri (2016)
Arnis Putri Rosyani, J500120030, 2012, THE CORRELATION OF SANITATION HYGIENE AND THE PRESENCE OF Escherichia coli BACTERIA IN REFILL DRINKING WATER DEPOTS AROUND MUHAMMADIYAH UNIVERSITY OF SURAKARTA. Background : Refill mineral water is one of the most consumed drinking water. It is influenced by the hygiene from the depot. Aim : Knowing the correlation between depot hygiene and the presence of Escherichia coli bacteria in water depots around Muhammadiyah University of Surakarta. Method : This study is observational analytic using cross sectional method. Hygiene sanitation using Peraturan Menteri Kesehatan Republik Indonesia Nomor 43 Tahun 2014. Result : The result showed 19 (52,8%) depots meet hygiene standard while the 17 (42,2%) didn't. There were 11 (30,6%) depots didn't meet the standard due to the presence of Escherichia coli bacteria in the water. So, there is correlation between depot hygiene and the presence of bacteria. It is suggested for the depot owners to control the hygiene and for the government to increase the awareness of controlling the quality of drinking water.